Vaccine candidate analysis of the helminth onchocerca volvulus: a computational approach / Mohd Nazri Mustafa - Mustafa, Mohd Nazri (2009)
Filarial nematode Onchocerca volvulus had been identified as the causative agent for river blindness, or onchocerciasis. A disease characterized by chronic skin and eye lesions. It is the world's second leading infectious cause of blindness. It is a major health problem in several tropical countries, mostly in Africa, south of the Sahara. More than 18 million persons are infected with this nematode. Discovery of primary FAR1_ONCVO gene in Onchocerca volvulus may provide us a deeper insight into vaccine development for river blindness. In this study, the identification of FAR1_ONCVO gene in Onchocerca volvulus was reported using in silica prediction approaches. FAR1_ONCVO gene of Onchocerca volvulus consists of 178 amino acids length. The predicted value of both pl and Mw of FAR1_ONCVO protein is 8.58 and 20580.81 Da, respectively. Prediction of secondary structure of Onchocerca volvulus FAR1_ONCVO protein revealed that it consists of 80.34% a-helix, 1.12% P-strand and 18.54% loop. Grand average of hydropathicity (GRAVY) is -0.516. Hence, Onchocerca volvulus FAR1_ONCVO protein is hydrophilic in nature. From the analyzed result, most of the protein sequences of Onchocerca volvulus FFAR1_ONCVO are located in extracellular cell. The region of "LRNFVKAKI" and "VIMANVVPF" which is at position 86 and 12 of FAR1_ONCVO protein sequences was predicted to have high potential candidate as promiscuous binders. In conclusion, the information obtained from in silica analysis of FAR1_ONCVO gene would then provide preliminary information for vaccine study.